POLA PERTUMBUHAN Staphylococcus aureus PADA MEDIA AGAR DARAH MANUSIA GOLONGAN O, AB, DAN DARAH DOMBA SEBAGAI KONTROL - Evy Diah Woelansari (Jurnal Ilmu dan Teknologi Kesehatan, 2016)
Blood Agar Plate (BAP) with sheep blood is the medium used for the identification and isolation of the bacterium Staphylococcus aureus. Because to produce is difficult, but is needed in health education institutions, BAP then used media as a human blood substitute. This study was to observe the pattern of growth of Staphylococcus aureus in media BAP human blood group O, AB and the blood of the sheep as a controle. With the aim to test the feasibility of using human blood group O and AB as essential compounds in the manufacture of a blood substitute sheep BAP media. Staphylococcus aureus growth patterns observed macroscopically to colony morphology, the number of colonies, and the diameter of the haemolysis zone. The suspension of bacteria used were pure cultures of Staphylococcus aureus (ATCC 25923) which is synchronized with Mc Farland 0.5 Standart solution, then do thinning 10-2. The suspension of bacteria that are already experiencing thinning planted in the media BAP human blood group O, AB and sheep blood each at 9 petri dish.From the observation of colony morphology, the number of colonies, and the diameter of the zone of haemolysis performed statistical tests using Kruskal Wallis test values obtained Asymp. Sig of 0.352 for the number of colonies and haemolysis zone diameters greater than α (0.05), which means there is no significant difference between the growth pattern of Staphylococcus aureus in media BAP using human blood group O, AB and sheep blood as a medium BAP controle.